Transformational Leadership in Smart Village Governance: Empirical Evidence from the Bangka Belitung Islands Province - Jhon Hendri; Harlis Setiyowati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the role of village heads' transformational leadership in promoting smart village governance through the digitalization of public services in the Bangka Belitung Islands Province. The research approach employed a descriptive qualitative approach, employing data analysis techniques modeled by Miles and Huberman (1994), through the stages of data reduction, data presentation, and conclusion drawing. Seven informants, consisting of village heads, village officials, and community members, were purposively selected to explore their direct experiences related to the implementation of digital systems at the village level. The results indicate that transformational leadership plays a crucial role in fostering motivation, innovation, and participation of village officials in the digitalization of public services. Four key dimensions—idealized influence, inspirational motivation, intellectual stimulation, and individual attention—shape collaborative and change-oriented work behavior. Digitalization contributes to increased transparency, accountability, and effectiveness of village governance, while strengthening public trust in the government. This study concludes that the success of smart village governance is determined not only by technology but also by the quality of transformational leadership, which is capable of driving social, ethical, and work culture change toward an adaptive, transparent, and sustainable village government.